2000
DOI: 10.1086/313996
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection in Long-Term-Care Facility Residents

Abstract: Urinary tract infection is the most frequent bacterial infection in residents of long-term-care facilities. Most infections are asymptomatic, with a remarkable prevalence of asymptomatic bacteriuria of 15%-50% among all residents. The major reasons for this high prevalence are chronic comorbid illnesses with neurogenic bladder and interventions to manage incontinence. Prospective, randomized, comparative trials of therapy and no therapy for asymptomatic bacteriuria among nursing home residents have repeatedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 27 publications
4
92
0
6
Order By: Relevance
“…Point prevalence rates have been reported at 1.58-3.8 in nursing homes 13,15 . The prevalence of asymptomatic bacteriuria is much higher, with rates of 15-50% in non-catheterised US residents of long term care facilities 22 and similar rates documented in other countries 23,24 .…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Point prevalence rates have been reported at 1.58-3.8 in nursing homes 13,15 . The prevalence of asymptomatic bacteriuria is much higher, with rates of 15-50% in non-catheterised US residents of long term care facilities 22 and similar rates documented in other countries 23,24 .…”
mentioning
confidence: 57%
“…It is commoner in women, with advancing age 28 , is associated with pyuria in over 90% of cases 22 , is inevitable in long-term catheterisation and has an incidence of 3-6%…”
Section: Bacteriologymentioning
confidence: 99%
“…UTIs are the most commonly reported bacterial infection in long-term care facilities, accounting for up to 50% of antibiotics used. [6][7][8] A large proportion of these cases are thought to represent asymptomatic bacteriuria. 8,9 Routine screening for asymptomatic bacteriuria is discouraged, because treatment of asymptomatic cases has not been shown to have any clinical benefit and may contribute to adverse drug reactions or re-infection with drug-resistant organisms.…”
Section: Antimicrobial Use In Urinary Tract Infectionsmentioning
confidence: 99%
“…8,9 Routine screening for asymptomatic bacteriuria is discouraged, because treatment of asymptomatic cases has not been shown to have any clinical benefit and may contribute to adverse drug reactions or re-infection with drug-resistant organisms. 6,7 At the study institution, a number of problematic practices were observed, including the submission of urine samples for culture for all admissions on one inpatient unit, irrespective of symptoms or signs, as well as the culturing of urine samples on the basis of appearance (e.g., cloudiness) and smell. At WPHC, registered nurses have the authority to send urine specimens for culture and sensitivity (C&S) testing under a medical directive.…”
Section: Antimicrobial Use In Urinary Tract Infectionsmentioning
confidence: 99%
“…Dotyczy ok. 10-20% kobiet powyżej 70. roku życia i jest szczególnie często diagnozowana u kobiet zamiesz-kujących w domach opieki, bo aż w 50% tej populacji [4,25]. Najczęściej nie jest związana z występowaniem objawów klinicznych [26]. Istnieje przekonanie, że bezobjawowa bakteriuria wieku starczego, poza wybranymi sytuacjami klinicznymi takimi jak planowane zabiegi diagnostyczne lub operacyjne w zakresie ukła-du moczowo-płciowego, włączając w to transplantacje nerek, nie powinna być leczona [27].…”
Section: Czynniki Dietetyczneunclassified